A review of epidemic preparedness for influenza through local vaccine production: national security for Thailand. Issue 10 (3rd October 2019) - Pitisuttithum, Punnee; Wirachwong, Ponthip
ABSTRACT: Being vigilant of the potential for an influenza pandemic, the Global Action Plan for Influenza Vaccines (GAP) promoted the establishment and maintenance of local vaccine manufacturing capacity. In accordance with this, the Thai government has developed its national strategic plan for influenza pandemic preparedness including the plan for manufacturing influenza vaccine in Thailand. With the support of WHO, the Thai Government Pharmaceutical Organization (GPO) as the developed local production capacity of influenza vaccines. The H1N1 live attenuated influenza vaccine (LAIV) and H5N2 LAIV produced by GPO have been proven to be safe and immunogenic through clinical trials, followed by Thai FDA licensure for pandemic use. The GPO-produced H5N2 LAIV has been proven to have priming effects on an inactivated subunit H5N1 booster vaccine. This Thai local manufacturer is now expanding its capacity to Inactivated Influenza Vaccine (IIV), aiming for sustainable influenza vaccine production for national coverage.